Synthesis, characterization and sensing properties of donor-acceptor systems based Dithieno[3, 2-b;2′, 3′-d]thiophene and boron. (August 2021) - Ipek, Ozgecan Savlug; Topal, Sebahat; Ozturk, Turan
Abstract: Two dithieno[3, 2- b ;2′, 3′- d ]thiophenes, posessing donor-π-acceptor (D-π-A) character through electron donor triphenylamine and electron acceptor boron, were successfully synthesized. They had large Stokes shifts of 140 and 155 nm and exhibited remarkable solvatochromic behaviors. Emission colors changed from blue to orange in non-polar to polar solvents, respectively. They acted as colorimetric and fluorescent chemosensors with high sensitivity towards fuoride anion, displaying a blue shift from yellow upon addition of TBAF as a result of blocking D-A conjugation. Graphical abstract: Image 1 Highlights: Two novel dithieno[3, 2- b ;2′, 3′- d ]thiophenes, having electron donor tetraphenylamine (TPA) and electron acceptor boron units. High fluoride anion sensing property through emission. Large Stokes shifts of 140 and 155 nm.